Pengaruh Shopping Lifestyle, Sales Promotion dan Price Discount Terhadap Impulse Buying Produk Fashion Dengan Positive Emotion Sebagai Variabel Moderasi Pada E-Commerce Tiktok Shop (Studi Kasus Pada Mahasiswa Universitas Kutai Kartanegara) - Iskandar; Sabran; Suprapto, Heru; Akbar, Ali; Zulhansyah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research aims to determine the influence of Shopping Lifestyle, Sales Promotion and Price Discount on Impulse Buying Fashion Products with Positive Emotion as a moderating variable in the TikTok Shop E-Commerce. This research was conducted with a case study of Kutai Kartanegara University students who used the TikTok application and shopped online. Primary Data is data used and sourced from respondents who filled out the questionnaire. Sampling was taken using quota sampling and purposive sampling techniques, where respondents were determined based on suitability of criteria with a minimum number of 384 people based on calculations using the Lemeshow formula. The analytical tool used in this research is Structural Equation Modeling (SEM) using Smart PLS Version 4 software. The results show that Shopping Lifestyle and Sales Promotion influence Impulse Buying of fashion products. Positive Emotion moderates Sales Promotion for Impulse Buying of fashion products. Price Discount and Positive Emotion do not have a significant effect on Impulse Buying of fashion products. Positive Emotion does not moderate Shopping Lifestyle and Price Discount on Impulse Buying of fashion products.